2020
DOI: 10.1080/07391102.2020.1841681
|View full text |Cite
|
Sign up to set email alerts
|

Pathway enrichment analysis of virus-host interactome and prioritization of novel compounds targeting the spike glycoprotein receptor binding domain–human angiotensin-converting enzyme 2 interface to combat SARS-CoV-2

Abstract: SARS-CoV-2 has become a pandemic causing a serious global health concern. The absence of effective drugs for treatment of the disease has caused its rapid spread on a global scale. Similarly to the SARS-CoV, the SARS-CoV-2 is also involved in a complex interplay with the host cells. This infection is characterized by a diffused alveolar damage consistent with the Acute Respiratory Disease Syndrome (ARDS). To explore the complex mechanisms of the disease at the system level, we used a network medicine tools app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The biological response of small molecules in a living organisms is largely regulated by their interaction partners (Sharan et al, 2007 ). The role of the interaction network becomes more important in computer aided drug design (CADD), since diseases are often reflected by alterations of protein complex of the certain pathways (Gollapalli et al, 2020 ; Oti et al, 2006 ). The cordycepin-protein network data revealed that cordycepin can modulate multiple pathways associated with apoptosis, cancer, hepatitis B, tuberculosis, influenza A, herpes simplex infection and many more.…”
Section: Resultsmentioning
confidence: 99%
“…The biological response of small molecules in a living organisms is largely regulated by their interaction partners (Sharan et al, 2007 ). The role of the interaction network becomes more important in computer aided drug design (CADD), since diseases are often reflected by alterations of protein complex of the certain pathways (Gollapalli et al, 2020 ; Oti et al, 2006 ). The cordycepin-protein network data revealed that cordycepin can modulate multiple pathways associated with apoptosis, cancer, hepatitis B, tuberculosis, influenza A, herpes simplex infection and many more.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, there has been some evidence indicating that quercetin exhibits anti‐coronavirus properties, mostly through its anti‐inflammatory effects (Valério et al, 2009 ). To enter human cells, the COVID‐19 virus, being an RNA‐based virus, recruits the angiotensin‐converting enzyme 2 receptors (hACE‐2) (Gollapalli et al, 2022 ). The COVID‐19 virus uses hACE‐2 to initiate cascades that lead to high levels of proinflammatory cytokines, reactive oxygen species, and eventually acute respiratory distress syndrome (Kuppusamy et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The cellular component of phagocytic vesicles (GO:0045335) was also mentioned in the context of SARS-CoV-2 infection and pulmonary fibrosis [ 35 ]. Additionally, the enriched molecular function GO:0042287, responsible for MHC protein binding was found in a recent SARS-CoV-2 study [ 36 ], based on an enrichment analysis in 76 selected neighbor proteins of the SARS-CoV-2 spike protein. In the EBI QuickGO database the term GO:0042287 is further described as ‘Binding to a major histocompatibility complex molecule; a set of molecules displayed on cell surfaces that are responsible for lymphocyte recognition and antigen presentation’.…”
Section: Discussionmentioning
confidence: 99%